Design of a short-time energy saving tank for light weight electric transport vehicles - Lobur, M.; Kulpa, M. (Видавництво Львівської політехніки, 2015)
Запропоновано підхід до проектування резервуару для колеса електромобіля, який має коротку енергозбережну дію. Обґрунтовано, що новий продукт буде не лише енергозбережним, але й дасть змогу зекономити потужність під час гальмування та набирання швидкості. Для проектування обрано спеціалізовані бібліотеки ПЗ CATIA, оскільки вони є найвідповіднішими для розв’язку питань машинобудування. The paper suggests the approach to the design of a short-time energy saving reservoir for light-weight electric transport vehicles. It is substantiated that the new product will be energysaving and will ensure gains in traction and braking force. CATIA was chosen as the most proper environment for the design as its libraries are the most suitable for machine-building.
Keywords: електромобіль; енергозбереження; колесо; резервуар; сенсор; CATIA; electromobile; power-saving; wheel; reservoir; dynamics; sensor; CATIA